Extracting Additional Influences From Physician Profiles With Topic Modeling: Impact on Ratings and Page Views in Online Healthcare Communities - Wei, Xiaoling; Hsu, Yuan-Teng (Frontiers in Psychology, 2022)
How physicians can get better ratings and more page views in online healthcare communities is an important issue. Based on 38,457 physicians’ profiles from a popular online healthcare community in China, we used Latent Dirichlet Allocation model, which is a common topic model, to analyze the non-English text to obtain more doctor’s latent characteristics. We found five of the most frequently mentioned topics. In addition to the first topic (doctor’s academic rank and practice name), “research ability”, “foreign experience”, “committee position”, and “clinical experience” were included as unstructured descriptions in the doctor’s profile. Inferences about physician ratings and page views could be improved if these themes were set as characteristics of physicians. Specifically, in our findings, Physicians’ mentions of their “research ability” and “foreign experience” had a significant positive impact on physician ratings. Surprisingly, physicians mentioning more “clinical experience” had a significant negative impact on physician ratings. Moreover, while descriptions about “foreign experience” and “committee position” had a significant positive impact on page views, physician mentions of “research ability” had a significant negative impact on page views. These results provide new insights into the ways in which online healthcare community managers or physicians create their personal online profiles.